Design of Triband Microstrip Antenna for Wlan/Wimax Applications - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2022)
Triband antenna is useful for various applications, such as WLAN, WIMAX and WBAN. To meet the requirements of the portable antenna, properties such as flexibility, cost and data rate must be considered. The paper details the design and simulation of a rectangular triband antenna using an electromagnetic simulator (CST), as well as the analysis of its performance with an FR-4 substrate. The antenna is designed with a dielectric constant material of 4.3 substrate for 2.4 GHz, 3.5 GHz and 4.4 GHz frequencies. Variables such as directivity, reflection coefficient, path loss and cost of the antenna in human model, in addition to the SAR of the antenna in the human body are also analyzed to be within international standards. © 2022 IEEE.